2018
DOI: 10.1002/ange.201802488
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the Polycyclic System in the Antifungal HSAF and Analogues from Lysobacter enzymogenes

Abstract: The biocontrol agent Lysobacter enzymogenes produces polycyclic tetramate macrolactams (PoTeMs), including the antifungal HSAF.T oe lucidate the biosynthesis of the cyclic systems,w ei dentified eleven HSAF precursors/ analogues with zero,o ne,t wo,o rt hree rings through heterologous expression of the HSAF gene cluster.Aseries of combinatorial gene expression and deletion experiments showed that OX3i st he "gatekeeper" responsible for the formation of the first 5-membered ring from lysobacterene A, OX1and OX2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…1). 8, 9 The structure of HSAF differs remarkably from those of existing fungicides on the market 10 . Because of its significant bioactivities and distinct structure, great efforts have been made to investigate the biosynthetic and regulatory mechanisms of HSAF 8, 9, 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). 8, 9 The structure of HSAF differs remarkably from those of existing fungicides on the market 10 . Because of its significant bioactivities and distinct structure, great efforts have been made to investigate the biosynthetic and regulatory mechanisms of HSAF 8, 9, 11 .…”
Section: Introductionmentioning
confidence: 99%
“… 8, 9 The structure of HSAF differs remarkably from those of existing fungicides on the market 10 . Because of its significant bioactivities and distinct structure, great efforts have been made to investigate the biosynthetic and regulatory mechanisms of HSAF 8, 9, 11 . In our previous studies, strategies including genetic modification and fermentation optimization have been investigated in an effort to improve the production of HSAF in L. enzymogenes strain OH11 12‐15 .…”
Section: Introductionmentioning
confidence: 99%
“…7A) also indicates that these substances contain a heat-stable factor. The HSAF family has structural diversity (Li et al, 2018) and the BGC in S10 has 75% similarity to the reported HASF (BGC0000999). Thus the heatstable factor in Streptomyces S10 could be a new HASF and probably has another biosynthesis pathway or uncharacterized mechanism that is different from bacteria (Su et al, 2018).…”
Section: Secondary Metabolite Analysis Of S10mentioning
confidence: 95%
“…Lysobacter enzymogenes is a nonpathogenic strain that was used to control crop fungal diseases known for the synthesis of an antifungal weapon (heat-stable antifungal factor, HSAF) that exhibits inhibitory activity against a wide range of fungal species [16][17][18][19][20][21][22][23] . Our previous work revealed that RpfG affects production of the antifungal weapon HSAF in L. enzymogenes 24 .…”
Section: Introductionmentioning
confidence: 99%